Targeted alveo‐pleural fistula endobronchial valve treatment using ventilation scintigraphy - Calvin Sidhu; Shoba Ratnagobal; Rajesh Thomas; Gary Y. C. Lee; Enya Drudy; Roslyn J. Francis (Respirology Case Reports, 2023)
Abstract Persistent air‐leaks can be difficult to localize in radiology. Bronchoscopic management of air‐leaks requires identification of the leak's location to allow suitable targeted treatment. One‐way endobronchial valves have become a suitable option for persistent air‐leaks. In this report, a combination scintigraphy and one‐way endobronchial valve treatment successfully resolved a persistent air‐leak.